2018
DOI: 10.1021/acs.jpcc.8b05812
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ni in Bimetallic PdNi Catalysts for Ethanol Oxidation Reaction

Abstract: Bimetallic PdNi catalysts have garnered great interest in the study of ethanol oxidation reactions (EORs), though mechanistic insights into their catalytic performances are lacking, which hinders further improvement and rational design of the next generation of PdNi catalysts. As such, density functional theory (DFT) calculations were performed for six key elementary reactions using four model catalysts, one with pure Pd and three for PdNi. DFT results indicate that the reduced catalytic activities observed ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 63 publications
4
41
0
Order By: Relevance
“…[12][13] As such, DFFCs currently need potential efficient and stable catalysts for widespread commer-cial applications. [17] When considering advancements in Pd-based anode catalysts for alkaline formate oxidation, transition metal alloying has been shown to increase the alcohol and formic acid/formate fuel oxidation capabilities [5,[18][19][20][21] and to the best of our knowledge, alkaline formate oxidation using Pd-transition metal alloy catalysts has seldom been studied and is largely unexplored. [14][15][16] However, there is an imminent need for performance improvements in Pd catalysts in terms of their efficiency and durability before they can be effectively utilized in alkaline DFFCs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13] As such, DFFCs currently need potential efficient and stable catalysts for widespread commer-cial applications. [17] When considering advancements in Pd-based anode catalysts for alkaline formate oxidation, transition metal alloying has been shown to increase the alcohol and formic acid/formate fuel oxidation capabilities [5,[18][19][20][21] and to the best of our knowledge, alkaline formate oxidation using Pd-transition metal alloy catalysts has seldom been studied and is largely unexplored. [14][15][16] However, there is an imminent need for performance improvements in Pd catalysts in terms of their efficiency and durability before they can be effectively utilized in alkaline DFFCs.…”
mentioning
confidence: 99%
“…Palladium is the catalyst that has shown the most promising prospects for enhanced liquid-fuel oxidation kinetics in alkaline media and that could effectively replace platinum. [17] When considering advancements in Pd-based anode catalysts for alkaline formate oxidation, transition metal alloying has been shown to increase the alcohol and formic acid/formate fuel oxidation capabilities [5,[18][19][20][21] and to the best of our knowledge, alkaline formate oxidation using Pd-transition metal alloy catalysts has seldom been studied and is largely unexplored. Previous reports suggest that the formate oxidation reaction on the Pd surface proceeds through the decomposition of COO À into CO 3 2À in alkaline medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Miao et al performed density functional theory (DFT) calculations on the PdNi catalysts. They found that when the estimated Ni atoms on the catalyst surfaces reached up to 77%, the PdNi catalysts could attain a complete EOR . Mondal et al fabricated PdCoNi/C by ethylene glycol reduction method.…”
Section: Introductionmentioning
confidence: 99%
“…They found that when the estimated Ni atoms on the catalyst surfaces reached up to 77%, the PdNi catalysts could attain a complete EOR. 10 Mondal et al fabricated PdCoNi/C by ethylene glycol reduction method. They described that the PdCoNi/C particles demonstrated higher EOR activity than Pd/C catalysts.…”
Section: Introductionmentioning
confidence: 99%